Frequency of dengue infection in febrile patients attended Dhaka Medical College Hospital during January to December, 2018 (Journal of Dhaka Medical College, 2020)
Introduction: Dengue is a major public health concern in our country. The alarming thing is that the seasonal trend of dengue infection is changing with time in Bangladesh due to climate change and unplanned urbanization. Our study was conducted to determine the frequency of dengue virus infection among the febrile patients in 2018 at Dhaka Medical College Hospital (DMCH) and to observe the seasonal trend.Materials and Methods: The study was carried out on 899 febrile patients attended in DMCH from January to December, 2018. Whole blood samples were collected and sera were tested for dengue NS1 antigen and anti-dengue IgM antibodies using commercial test kits (NS1 by OMC Healthcare (Pvt.) Ltd & IgM antibody by Omega Diagnostics Ltd.), respectively. All negative dengue cases were tested for anti Chikungunya antibody to exclude chikungunya.Results: Of the total 899 febrile patients, 350(38.93%) were positive for Dengue infection. Out of them 264(75.43%) were positive for NS1, 82 (23.43%) were positive for IgM and 4 (1.14%) were positive for dengue NS1antigen + anti dengue IgM antibody. More than 50% patients belonged to age group 15-29 years. Males were predominant. More than 60% cases were detected in the post monsoon season.Conclusion: Highest dengue cases were detected in this year in comparison to the previous year’s probably due to re-emergence of DEN-3 serotype. Due to pattern of climate change, seasonal trend of dengue infection was not maintained. Moreover, unplanned urbanization and poor solid waste management have worsened the situation more.J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 105-111